Codes Detecting and Correcting Solid Burst Errors - Pankaj Kumar Das (Institute of Advanced Engineering and Science, 2012)
This paper studies linear codes capable of detecting and correcting solid burst error of length b or less. The lower and upper bounds on the number of parity-check digits required for such codes are obtained. Illustrations of codes for detecting as well as correcting such errors are provided.